Development and characterisation of SMURF2-targeting modifiers. (1st January 2021) - Manikoth Ayyathan, Dhanoop; Levy-Cohen, Gal; Shubely, Moran; Boutros-Suleiman, Sandy; Lepechkin-Zilbermintz, Veronica; Shokhen, Michael; Albeck, Amnon; Gruzman, Arie; Blank, Michael
Abstract: The C2-WW-HECT-domain E3 ubiquitin ligase SMURF2 emerges as an important regulator of diverse cellular processes. To date, SMURF2-specific modulators were not developed. Here, we generated and investigated a set of SMURF2-targeting synthetic peptides and peptidomimetics designed to stimulate SMURF2's autoubiquitination and turnover via a disruption of the inhibitory intramolecular interaction between its C2 and HECT domains. The results revealed the effects of these molecules both in vitro and in cellulo at the nanomolar concentration range. Moreover, the data showed that targeting of SMURF2 with either these modifiers or SMURF2 -specific shRNAs could accelerate cell growth in a cell-context-dependent manner. Intriguingly, a concomitant cell treatment with a selected SMURF2-targeting compound and the DNA-damaging drug etoposide markedly increased the cytotoxicity produced by this drug in growing cells. Altogether, these findings demonstrate that SMURF2 can be druggable through its self-destructive autoubiquitination, and inactivation of SMURF2 might be used to affect cell sensitivity to certain anticancer drugs.